Pengaruh Pelatihan dan Lingkungan Keluarga terhadap Minat Berwirausaha pada Lulusan Balai Latihan Kerja Subulul Huda - Haya Nabila; Nurma Fitrianna (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2024)
Interest in entrepreneurship is a person's interest in doing independent business activities. When someone has done something graphic design skills training, his entrepreneurial interest should increase; BLK Subulul Huda aims to improve the quality of human resources and the competitiveness of Indonesian workers needed in the business and industrial world. The method used in this study is a quantitative method, using multiple linear regression analysis with data collection techniques in the form of distributing questionnaires to 60 Subulul Huda Job Training Center (BLK) graduates. The sampling technique applied in this study is non-probability sampling. The results of this study show that partial training has a positive and significant effect on entrepreneurial interest. The family environment partially has a positive and significant effect on entrepreneurial interest. Training and family environment simultaneously affect entrepreneurial interest in graduates of the Subulul Huda Job Training Center (BLK).